AQUATIC PLANT (HYDRILLA VERTICILLATA) ROLES IN BIOACCUMULATION OF HEAVY METALS - & Al-Tabatabai, Al-Zurfi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The current study was aimed to test the ability of Hydrilla verticillata plant ability to accumulated of cadmium and lead in its tissues. The plant was treated with different concentrations of cadmium (1,2,4,8) ppm and lead (0.5,5,10,20) ppm for 21 days’. The concentration of metals was measured in plant and water, Bioaccumulation factor and removal ratio were also measured during days (1,7,14,21), as well as measured biomass and length of the plant were measured at the end of the experiment. The results were shown that the highest cadmium and lead removal rate were (77, 88) % at concentration (4, 10) ppm during (21, 7) days, respectively, also the bioaccumulation factor (BCF) of the two metals were (21639 and 45467) at concentrations (4 and 0.5) ppm during the 21st day of the experiment respectively. The biomass of plant in treated aquarium with different concentrations of cadmium showed a decrease during the experimental days, while increased in biomass of plant treated aquarium with different concentrations of lead. The length rate of the plant was significantly reduced in the plant that treated with cadmium but significant increase in plant treated with lead compared to the control.